Relationship between Adiponectin Level, Insulin Sensitivity, and Metabolic Syndrome in Type 1 Diabetic Patients - Kristina Blaslov; Tomislav Bulum; Karin Zibar; Lea Duvnjak (International Journal of Endocrinology)
Objective. Adiponectin is known to be decreased in insulin resistance (IR) and metabolic syndrome (MS) which can be present in patients with type 1 diabetes mellitus (T1DM). The aim of this study was to evaluate the relationship between adiponectin level, MS, and insulin sensitivity in T1DM. Research Design and Methods. The study included 77 T1DM patients divided into two groups based on the total plasma adiponectin median value. Insulin sensitivity was calculated with the equation for eGDR, and MS was defined according to International Diabetes Federation criteria. Results. Patients with higher adiponectin level () had significantly lower waist circumference (), fasting venous glucose levels (), higher HDL3-cholesterol (), and eGDR () in comparison to the group with lower adiponectin who showed higher prevalence of MS (). eGDR increased for 1.09 mg/kg−1 min−1 by each increase of 1 µg/mL total fasting plasma adiponectin (). In the logistic regression model, adiponectin was inversely associated with the presence of MS (). Conclusion. Higher adiponectin concentration is associated with lower prevalence of MS in T1DM. Whether higher adiponectin concentration has a protective role in the development of the MS in T1DM needs to be clarified in future follow-up studies.